The Structure and Role of Segment 7 (Matrix Protein) and Segment 8 (Non Structural) in The Life Cycle and Virulence of Influenza Virus - N.L.P. Indi Dharmayanti (Indonesian Center for Animal Research and Development, 2010)
Matrix (M) and Non Structural (NS) proteins are smallest segments of influenza virus genome. The noncoding sequences at each end include the sequences of 11 – 13 nucleotides at the 5’ ends and 9 – 11 nucleotides at the 3’ end which are highly conserved between seven or eight different RNA segments and very similar for A, B and C influenza viruses. Protein of M1 is an essential structural component of the virion and participates in other steps during the replication of influenza virus. During early viral infection, dissociation of M1 from RNP is required for entry of viral RNP into the cytoplasm of the host cell. On the other hand, NS1 is a multifunctions protein that performs a plethora of activities, which may additionally contribute toward efficient virus replication and virulence during infection. The role of NS1 are temporal regulation of viral RNA synthesis, control of viral mRNA splicing, enhancement of viral mRNA translation, regulation of virus particle morphogenesis, suppression of host immune/apoptotic responses, activation of phosphoinositide 3–kinase (PI3K); and involvement in strain-dependent pathogenesis. This paper reviews the structure and role of two proteins i.e. Matrix and Nonstructural to understand the character of influenza virus especially in virulence and pathogenesis ability of virus other than hemagglutinin (HA) and neuraminidase (NA) protein as known. Key words: Influenza virus, matrix protein, non structural protein